Il mestiere di decidere. Magistero cattolico e libertà di coscienza del fedele (Stato, Chiese e pluralismo confessionale, 2013)
contributo sottoposto a valutazioneSOMMARIO. 1. Premessa: sul libero arbitrio - 2. La “Nota dottrinale circa alcune questioni riguardanti l’impegno e il comportamento dei cattolici nella vita politica” della Congregazione per la Dottrina della Fede (2002) - 3. Il concetto di fede e cultura cattoliche come unità inscindibili. L’affermazione di valori “non negoziabili” e il richiamo alla legge naturale. Il possibile conflitto tra “Chiesa della gerarchia” e “Chiesa della comunità” e la dialettica Magistero-coscienza personale - 4. Conclusioni.  ABSTRACT This essay is about the conflict between the teachings of the Catholic Church and the status of the believer as a subject possessing freedom of conscience. It addresses several issues which concern the believer’s claim to freedom of conscience in making moral choices, and the observance of "unquestionable principles" required by the catholic hierarchy as fundamental for the Catholic faith within a moral context. Among the various questions, it underlines the conceptual problems in demanding the respect of a "catholic culture", due to the polysemous nature of the word "culture" and the transcultural aspiration of Catholic doctrine, and in asserting the existence of a "natural law" while soliciting the respect of undisputable moral values.